A study of the criteria teachers use when selecting learning material - Koch, Lynn (Rhodes University, Faculty of Education, Department of Education, 2004)
This study investigates the criteria teachers use when selecting and evaluating learning support material, in particular, English second language textbooks. The study seeks to determine what informs the criteria that teachers use for selection. The study is conducted against the backdrop of Curriculum 2005 (C2005) and outlines the C2005 revision process and the subsequent introduction of the Revised National Curriculum Statement (RNCS). Through a series of focus group interviews, the researcher explores the criteria teachers use for evaluation. Many of the teachers in this study did not have clearly articulated criteria; rather, they drew on implicit criteria and mentioned favoured qualities or attributes that they looked for in a textbook. In addition, the teachers in the focus groups used criteria that had been 'told' rather than 'owned' and had not developed their own sets of criteria. This research concludes that teachers are caught between two conflicting sets of criteria: those of their pre-service training and those of the new curriculum, which is currently being mediated to them through brief orientations. Drawing on recent literature, the researcher argues that in order to shift deep-seated literacy practices, teacher training needs to be prolonged, in-depth and ongoing.
Keywords: Textbooks -- South Africa -- Evaluation; Curriculum planning -- South Africa